KEBIJAKAN PROGRAM POJOK ASI UNTUK TERCAPAINYA ASI EXCLUSIVE PEGAWAI RUMAH SAKIT UMUM DAERAH (RSUD) I LAGALIGO KABUPATEN LUWU TIMUR - Endang Susilowati; Frida Chairunisa; Muh. Syarif Ahmad (Jurnal Administrasi Negara, 2021)
The main problem in this research is the policy of the breastfeeding corner program for employees at Lagaligo I Hospital, East Luwu Regency to achieve exclusive breastfeeding. The purpose of this research is to find out and analyze the breastfeeding corner policy for employees at Lagaligo I Hospital, through predisposing, enabling and reinforcing factors. This research was conducted with a qualitative approach and descriptive methods. The data collection techniques used were through observation, interviews and document review and then analyzed in depth to answer problems related to the ASI corner program policy for employees at Lagaligo I Hospital. The results showed that the policy of the breastfeeding corner procurement program for employees at Lagaligo I Hospital: (1) Predisposing the ASI corner at Lagaligo I Hospital, the policy makers really understand the importance of the ASI corner space, where the regulatory system requires that RSUD I lagaligo as a service provider The public prepares a breastfeeding corner so that every female worker can increase the percentage of breastfeeding, maintain the value of privacy and support the health of mothers and babies. (2) The facilitators of Lagaligo I Hospital have staff who are trained to educate women workers who are breastfeeding and the availability of alternative rooms or facilities and infrastructures to support the achievement of exclusive breastfeeding and the location of the room which is a very strategic breastfeeding corner. Apart from the availability of regulations, female workers who are breastfeeding have received support from family, co-workers and the availability of trained staff to provide education.